Uma abordagem crítica para a educação a distância orientada para as microfinanças - Birochi, Renê (2011)
Investigations on distance education practices, and the respective uses of media for this application, hark back to correspondence courses of the 19th Century. Distance education (DE) mediated by information and communication technologies (ICTs) is a recent development characterized by a post-industrial society which exploits a broad array of resources, processes and media to promote education. Historically, the DE domain has been the subject of scant theoretical studies investigating the framework underlying DE practices. The literature also reveals an almost total absence of approaches based on the traditions of critical thinking, such as the theory of structuration (GIDDENS, 1984) and critical pedagogy (FREIRE, 1987). Against this background, an analytical review of these approaches was carried out, relating them to DE. The aim of this review was to contribute to the discussion on the theoretical foundations of DE, first established in 1960, in a bid to broaden the scope of DE practices. Indeed, mechanisms typical of an industrial society still predominate in DE, such as mass replication of educational content. In order to address this issue, an examination of the core theories of DE was conducted seeking to identify a common theoretical framework, underpinned by a few seminal concepts. The concepts which emerged in the analysis were reinterpreted in the context of critical traditions, drawn from the disciplines of philosophy, sociology, education and communication. This parsimonious process of conceptual review of DE was enriched by the inclusion of two additional lines of investigation: adult education and financial education. The review process culminated in the devising of a theoretical framework which served as the central core of this investigation. The framework underwent major influences and substantive changes, stemming from the empirical field of investigation. The empirical field represented an opportunity to investigate the main focus of this thesis, namely, to elucidate how DE programs should be structured in order to act as instruments of socioeconomic emancipation of business owners that are, in turn, users of microfinancial services. In order to address this theme, an instrumental case study was performed based on qualitative research methods and procedures. The municipality of Autazes in the state of Amazonas was elected as the target of this study, given its recent significant socioeconomic growth following installation of points of access to financial services enabled by ICTs. This growth led to economic development together with worsened social tensions, including increased indebtedness of the population. The municipality also boasts a distancebased public education network provided by the government of the state of Amazonas, an initiative which has garnered several recognized international awards. The theoretical and empirical contributions of this study have been consolidated into a final theoretical framework which may serve as a basis for devising new critical theories in DE. Finally, a new model of critical DE was proposed, aimed specifically at the practice of this mode of education.